EVALUATION OF Zr, Ni-Cr, And Au-Ag APPLIED MATERIALS USING FEM ON PROSTHETIC CROWNS - P Vicky Kumar,; Anil Kumar Birru,; Muthu, Nelson (Malaysian Journal of Science, 2023)
The crown is a steady prosthesis designed to restore the functionality of a damaged tooth along, with its shape and size. They are also used to reinforce the tooth that poses long-term risk due to wide cavities and accidental injuries. The crowns are fixed using dental cement made of different materials such as porcelain cement, ceramics, etc. The present work aims to assess the mechanical properties – stiffness and strength, of the single molar crown prosthetic tooth materials to determine the efficacy of each material under typical masticatory load observed in clinical settings. To this end, the finite element method (FEM) is used to analyze the mechanical behavior of the molar crowns made of Zirconium (Zr), Nickel Chromium (Ni-Cr), and Gold alloy (Au-Ag). The crown models were created in Solidworks and exported to the ANSYS FE package. The exported three-dimensional models were subjected to varying loading conditions – vertical and oblique forces to the tooth axis under suitable displacement boundary conditions. Due to a relatively high elastic modulus, the Zr and Ni-Cr alloy exhibited a higher stress concentration and lower deformation on the crown’s intaglio surface compared to the Au-Ag alloy.